The Most Monstrous Kind of Art: Frankenfictions - Limpár, Ildikó (Hungarian Journal of English and American Studies, 2020)
Book review:de Bruin-Molé, Megen. Gothic Remixed: Monster Mashups and Frankenfictions in 21st-Century Culture. London: Bloomsbury Academic, 2019. x + 264 pages. ISBN 978-1350103054. Hb. £76.50.